PROGRAM KAMPUNG TERNAK DOMPET DHUAFA BANTEN DALAM MENINGKATKAN EKONOMI UMAT - Itang, Itang; Baihaqi, Wazin (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
This research discusses the livestock village program developed by Dompet Dhuafa Banten in improving the economy of the people. As with its vision and mission, Dompet Dhuafa Banten has the goal of being able to create a prosperous society, one of which is through the livestock village program as part of the Dompet Dhuafa Banten assistance program by functioning the management of zakat, infaq and shodaqoh funds. The research method used in this study is to use a descriptive research method with a qualitative approach. Some of the findings that can be raised in this study are that the Dompet Dhuafa Banten cattle village program consists of several activities carried out, namely by financing livestock banks, caring for livestock, internships for finished farmers, providing training to farmers and stocking sacrificial animals. In addition, it can also be known that the management of livestock villages is carried out based on the principle of mudharabah, where the shohibul mal in this case is Dompet Dhuafa Banten while as the shohibul mudharib party is the farmer, whose results will be divided equally according to the agreement at the time of the contract. Another thing obtained from the results of this study is that the Dompet Dhuafa Banten cattle village program makes a positive contribution, in this case it is proven that the Dompet Dhuafa Banten cattle village program can improve the economy of the people with a significant increase